KONTRIBUSI HASYIM ASY’ARI PADA PENDIDIKAN ISLAM - Mukani, Mukani (TA'LIMUNA: Jurnal Pendidikan Islam, 2015)
The intention of pesantren Tebuireng establishment in 1899 aimed to produce the Islamic scholars who have a sense of nationalism. The establishment preceded for 13 years before Nahdatul Ulama established in 1926, whereas madrasah or school was one important thing to fight for as it was considered has paramount value for the nation. Through Jihad resolution, Hasyim Asy’ari (1945) confirmed the important role of education. The fatwa asserted on October 22, 1945, constituted a proof of his contribution to education. Indonesian education was believed that it won’t be conducted as well in colonialism. Hashim Ash'ari came forth with at least twenty one inscriptions in the form of book and treatise, which was dedicated to the advancement of in Indonesian education.